COMMENTS ON THE 1957 REVISION OF CORPORATE ACCOUNTING AND REPORTING STANDARDS. - Kelley, Arthur C. (The Accounting Review, 1958)
Abstract The 1955 American Accounting Association Committee assigned to the task of revising the 1948 Statement of Corporate Accounting Standards undoubtedly spent much time and effort in making this revision, and the bulk of their achievement is to be highly commended. However, there is one conclusion that is most surprising and disappointing, and could only cause confusion in the minds of the readers of corporate accounting statements. This is the statement with regard to Part IV, Income Determination, as follows: Interest charges, income taxes, and true profit sharing distributions are not determinants of enterprise net income. The profession is now faced with this surprising and really confusing recommendation of the Committee that corporate net income should not take into consideration interest charges, income taxes or profitsharing distributions. However to argue that interest charges and income taxes are not costs of carrying on a business enterprise and determinants of net income, is to propose a concept of corporate net income which is illogical, contrary to common sense and contrary to universal business practice.